Cultivating Metacognitive Resilience for Adaptive Learning and Academic Integrity in Post-Pandemic Higher Education - Teti Berliani; Pierre Marcello Lopulalan; Rabbani Ischak; Rachmat Efendi (Asian Journal of Applied Education (AJAE), 2026)
The post-pandemic shift in higher education requires students to develop strong metacognitive resilience to adapt effectively to hybrid learning while maintaining academic integrity. This study examines the relationship between metacognitive resilience, adaptive learning ability, and commitment to academic integrity among university students in Banten Province. Using a mixed-methods sequential explanatory design, quantitative data were collected through a survey of 60 purposively selected students, followed by in-depth interviews to enrich the findings. Data were analyzed using descriptive, correlational, and thematic techniques. The results indicate that metacognitive resilience significantly enhances students’ ability to adjust learning strategies and uphold ethical academic behavior in digital learning environments. Students with higher reflective awareness demonstrate greater flexibility in addressing online learning challenges and stronger consistency in maintaining academic honesty. The study highlights the importance of strengthening metacognitive literacy and academic ethics as foundations for sustainable adaptive learning in post-pandemic higher education.